Implementasi Ekstrakurikuler Kepramukaan Dalam Menanamkan Sikap Disiplin Dan Tanggung Jawab Siswa Kelas V UPT SDN 10 Kelara Kabupaten Jeneponto - Muh Yusran Nur; Muhammad Nawir; Fitri Yanty Muchtar (LPPM Politeknik Pratama, 2024)
The aim of this research is to determine the implementation of scouting extracurriculars in instilling an attitude of discipline and responsibility in class V students at UPT SD Negeri 10 Kelara. This thesis uses a qualitative descriptive research method with a case study approach which aims to describe or reveal scouting extracurricular activities at school. Researchers conducted research at the UPT SDN 10 Kelara location, precisely in Borong Loe Village, West Tolo Village, Kelara District, Jeneponto Regency. The informants used to obtain information in this research were 8 people consisting of the principal, class teacher, scout leader and 5 class V students. The researchers used three data collection techniques, namely observation, interviews and documentation. The results of research from extracurricular scouting activities in instilling an attitude of discipline and responsibility have had a significant impact on students at UPT SDN 10 Kelara to develop their character for the better with a series of scouting activities that are usually carried out such as making stretchers, memorizing the basic principles, carrying out PBB movements, connecting sticks and singing Islamic scout chants. Through several scouting activities carried out, the character of discipline and responsibility will be instilled in students. The school and the students' parents will be very proud and happy if the students' character from previously not good to very good can change by participating in scouting extracurricular activities.